Peningkatan Kesejahteraan Masyarakat Melalui Partisipasi dan Implementasi Kebijakan dengan Efektifitas Pembangunan Program Dana Desa sebagai Variabel Intervening - Elvina Elvina; Musdhalifah Zebua (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
The purpose of this study was to find out how the influence of community participation, implementation, and effectiveness on community welfare, both directly and indirectly. The population in this study were the head of households in Siburbur Village, Subdistrict of Dolok, North Padang Lawas Regency, totaling 132 Household Heads. The sampling technique was carried out using Proportional Random Sampling method, the sample was calculated using the Slovin formula, obtained as many as 101 household heads. Path Analysis used to analyze data, Data processing is assisted with the AMOS program. The results showed that all hypotheses proposed in this study were accepted. This means that there is a positive and significant influence between community participation, implementation of policies and the effectiveness of project on the welfare of the community, both directly and indirectly on the welfare of the community. The path coefficient of community participation has the greatest influence on welfare. This means that community participation is a very important factor in improving community welfare